2018
DOI: 10.1161/strokeaha.118.020827
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blood Pressure in the Early Phase of Ischemic Stroke and Stroke Subtype on Poststroke Cognitive Impairment

Abstract: URL: https://www.chictr.org. Unique identifier: ChiCTR-TRC-14004804.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 37 publications
5
22
0
Order By: Relevance
“…Research on the impacts of different etiologic stroke subtypes on the prevalence and severity of PSCI could provide new insights into the underlying mechanisms for the development and course of PSCI and, thereby, on its prevention and treatment. In agreement with several studies but in contrast to others, we found better outcomes among SVD patients than among the other stroke subtypes, as attention was most impaired in relation to cortical infarcts (CE and LAD) (17,23). We used the TOAST classification (22) to assess the etiologic subtype of ischemic stroke, which, to a small extent, reflects the severity and localization of the stroke and is known to be important for cognitive function (6,17,18,22).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Research on the impacts of different etiologic stroke subtypes on the prevalence and severity of PSCI could provide new insights into the underlying mechanisms for the development and course of PSCI and, thereby, on its prevention and treatment. In agreement with several studies but in contrast to others, we found better outcomes among SVD patients than among the other stroke subtypes, as attention was most impaired in relation to cortical infarcts (CE and LAD) (17,23). We used the TOAST classification (22) to assess the etiologic subtype of ischemic stroke, which, to a small extent, reflects the severity and localization of the stroke and is known to be important for cognitive function (6,17,18,22).…”
Section: Discussionsupporting
confidence: 84%
“…LAD and CE strokes are often cortical strokes of large volume, while SVD strokes are subcortical and of small volume ( 22 ). Cognitive impairment has been shown to be less common in the early post-stroke period in SVD compared to other stroke subtypes, but SVD is associated with cognitive decline long after a stroke ( 16 , 17 , 23 , 24 ). However, in their review and meta-analyses, Makin et al found similar proportions to have PSCI in lacunar vs. non-lacunar stroke [OR 0.75 (95% CI 0.47–1.20)] ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…While there is little evidence to support a specific BP threshold, there is a precedent for pre-activity BP screening criteria. A recent study in 708 post-ischemic stroke patients demonstrated increased odds of cognitive impairment at 3 months for patients in the lowest and highest systolic BP (SBP) quintiles within 7 days of stroke (Q1, 102–127 mmHg and Q5, 171–215 mmHg), relative to the middle quintile (Q3, 143–158 mmHg) after adjustment (55). Similarly, better outcomes were observed for patients in the middle quintile of diastolic BP (DBP) (Q3, 93–102 mmHg).…”
Section: Peripheral and Cerebral Circulatory Considerations For Exercmentioning
confidence: 99%
“…◦ People with tightly controlled blood pressure (e.g., SBP below 120 mmHg and/or DBP below 80 mmHg in ischemic stroke) (55). Refer to Guideline 1.0 for lower blood pressure limits prior to commencing early mobilization/exercise prescription.…”
Section: Mobilization and Aerobic Exercise In The Hyper-acute And Acumentioning
confidence: 99%
“…Actually, some randomized controlled trials of blood pressure lowering in hypertension have yielded to an improvement of cognitive decline [1820]. Increased blood pressure at the acute phase of stroke has been reported to increase the probability and severity of poststroke dementia [21], while the impact of chronic hypertension is still a matter of debate [22, 23].…”
Section: Introductionmentioning
confidence: 99%